PENGARUH DISIPLIN, BIMBINGAN DAN KEGIATAN MGMP TERHADAP KINERJA GURU SMP NEGERI 1 TAWANGHARJO KABUPATEN GROBOGAN - Minarni, Sri -; Triyaningsih, SL - (Universitas Slamet Riyadi, 2011)
ABSTRACT This study aimed to analyze the effect of a significant relationship between: (1) Master's Discipline to Performance, (2) Guidance for Teacher Performance, (3) the Teacher Performance Working Group activity, (4) the dominant variable effects on teacher performance SMP Negeri 1 Tawangharjo District Grobogan in 2010). Population and simultaneously sampled in this study were all teachers SMP Negeri 1 Tawangharjo Grobogan District in 2010 some 43 people. The data collection technique using a questionnaire with validity and reliability. Engineering analysis using classical assumption test, multiple linear regression, t test, F test and the coefficient of determination using SPSS. Conclusion The results of this study were (1) there is a significant influence on the performance of teacher discipline, (2) there is no significant effect on the performance of teachers' guidance, (3) there is a significant influence on the performance of teachers MGMP activities, and (4) are MGMP is the dominant factor affect teacher performance SMP Negeri 1 Tawangharjo Grobogan district. Keywords: displicine, guidance, involvement in teacher working group, teacher performance